The Exploration of Lithner’s Creative And Imitative Mathematical Reasoning Analysis Based on High School Student’s Mathematical Anxiety in Trigonometry Class - Lakshita, Argha; Meiliasari; Abdul Azis, Tian (JURNAL RISET PEMBELAJARAN MATEMATIKA SEKOLAH, 2024)
This study aims to explore the creative and imitative reasoning process of high school students based on their mathematics anxiety (MA) level. The research method used was descriptive qualitative research. The subjects selected were 6 students, with the criteria of high/medium/low MA questionnaire results. Data collection techniques were conducted by written tests, field observations, and interviews. The results of MA levels are 19.4% low level and 80.6% medium level of MA. The absence of high MA level students made the researchers investigate through the three aspects of MA, which are: Attitudinal, Cognitive, and Somatic. There were no significant differences within the other two aspects but the somatic aspect shows 36% amongst the medium level MA are having high category on this aspect: 1) Creative reasoning process is only owned by students with medium level MA; 2) Students with high level and low level MA are considered vulnerable to misconceptions, rely heavily on available information, and tend to find it difficult to make new approximation; 3) The process of Imitative reasoning is possessed in each MA category, judging from the performance of solving Algorithmic and Memorized type problems. Thus, it can be concluded that the type of reasoning of a student will differ between types of MA categories and with different processes according to their particular interest in learning.